2021
DOI: 10.1186/s13018-021-02657-2
|View full text |Cite
|
Sign up to set email alerts
|

Is the fusion order of the cranial and caudal levels different in two-level anterior cervical discectomy and fusion for cervical spondylopathy? A retrospective study

Abstract: Study design Retrospective study. Objective This study aimed to compare the fusion order between the cranial and caudal levels in two-level anterior cervical discectomy and fusion (ACDF) with a zero-profile device in the treatment of cervical spondylopathy. Summary of background data Fusion is the standard used to judge the success of ACDF. However, the fusion order in two-level ACDF remains uncertain.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 33 publications
2
8
0
Order By: Relevance
“…Previous studies reported that the rate of cage nonfusion after ACDF was less than 10% at 1‐year follow‐up 32 . However, in the early period after ACDF (during the first 90 days postoperatively), the fusion rate was much lower (15%–62%) at 3‐month follow‐up 33–36 . Lower fusion rates in the early period would result in higher rates of subsidence, cage displacement, and pseudarthrosis.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Previous studies reported that the rate of cage nonfusion after ACDF was less than 10% at 1‐year follow‐up 32 . However, in the early period after ACDF (during the first 90 days postoperatively), the fusion rate was much lower (15%–62%) at 3‐month follow‐up 33–36 . Lower fusion rates in the early period would result in higher rates of subsidence, cage displacement, and pseudarthrosis.…”
Section: Discussionmentioning
confidence: 98%
“…Following radiographic recommendations for evaluating cervical fusion, 39,40 fusion was defined as the presence of continuous bone bridges behind the surgical segments on CT three‐dimensional reconstruction. According to our previous study, ‘fusion’ is defined as the presence of ≤2°or 3°motion and/or ≤2 mm of motion of the interspinous distance on flexion–extension X‐rays 33–36,41 . Further, different implant and surgical procedures, as well as screw length and angle, would result in a different fusion rate 9 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The exclusion criteria were as follows: (1) previous cervical surgery; (2) ossification of the posterior longitudinal ligament or stenosis of the cervical spinal canal, spinal fracture, severe osteoporosis, or a history of metabolic bone disease; (3) local infection and ulceration of the neck skin, systemic inflammatory disease, rheumatoid arthritis, uncontrolled diabetes, or malignant tumor; (4) a psychological disorder preventing compliance with study requirements as described above; (5) poor general condition, serious diseases of important organs, or substantial risk associated with surgery (American Society of Anesthesiologists classification ‡IV); (6) continuous immunosuppressive therapy for >1 month within the previous 12 months; (7) hypersensitivity to the implant material (polyetheretherketone or titanium alloy); (8) severe obesity; (9) a history of drug abuse; (10) pregnancy or planned pregnancy during the study; and (11) participation in another clinical study that may have an impact on the outcomes of this study.…”
Section: Patient Populationmentioning
confidence: 99%
“…However, the early fusion rates (at 3 and 6 months postoperatively) are often unsatisfactory. According to available reports 8-12 , the 3-month and 6-month fusion rates have ranged from 2.9% to 43.1% and 30% to 68.8%, respectively. Although a lack of fusion may be asymptomatic, it may potentially lead to complications 13,14 , even a reoperation.…”
mentioning
confidence: 99%